Technical trading rules in the cryptocurrency market - Grobys, Klaus; Ahmed, Shaker; Sapkota, Niranjan (Elsevier, 2020)
This paper studies simple moving average trading strategies employing daily price data on the eleven most-traded cryptocurrencies in the 2016–2018 period. Our results indicate a variable moving average strategy is successful when using the 20 days moving average trading strategy. Specifically, excluding Bitcoin the technical trading rule generates an excess return of 8.76% p.a. after controlling for the average market return. Our results suggest that cryptocurrency markets are inefficient.
Keywords: technical analysis; cryptocurrency; Bitcoin; financial technology; FinTech; currency; electronic money; research financing; foreign exchange market; security market; means of payment; financial markets; marketing; finance; Internet; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|